Relevansi Agama dan Kemiskinan; Upaya Memahami Kemiskinan Secara Multidimensional dan Solusi yang Ditawarkan dalam Ekonomi Islam - Melis Melis (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2019)
AbstractIslam has warned its people not to be unemployed so that it slips into poverty because it is feared that with poverty someone will do anything, including harming others to meet their needs. There is a hadith which says